RELATIONSHIP OF LONG OPERATION WITH SHIVERING EVENTS IN POST SPINAL ANESTHETIC PATIENT AT RSUD LEUWILIANG BOGOR REGENCY - Taufik Romansyah; Adiratna Sekar Siwi; Suci Khasanah (Jurnal Cakrawala Ilmiah, 2022)
Shivering is a complication of spinal anesthesia with an incidence of up to 33-57%. The long duration of surgery causes the anesthetic procedure to be longer. This will increase the time of exposure of the body to cold temperatures and cause the effect of accumulating drugs and anesthetic agents. Data on surgical patients at Leuwiliang Regional Hospital from December 2021 to February 2021, namely 60% of patients underwent surgery <1 hour, 20% underwent 1-2 hours of surgery, and 20% underwent >2 hours of surgery. The incidence of shivering at Leuwiliang Regional Hospital is 5 out of 10 patients (50%). The study aimed to determine the relationship between the duration of surgery and the incidence of shivering in patients after spinal anesthesia at Leuwiliang Hospital, Bogor Regency. The research method uses a type of analytics that is cross-sectional. The population in this study was 1212 respondents. The sampling technique in this study used purposive sampling techniques for 92 respondents.The data was taken by making observations to respondents. The results showed that the duration of the operation was 1-2 hours as many as 51 respondents (55.4%). The incidence of shivering in patients after spinal anesthesia found that there was a degree 3 shivering of 54 respondents (58.7%). There is a long association of surgery with the incidence of shivering in post-spinal anesthesia patients with a p-value of 0.001 (P<0.05). To Leuwiliang Hospital, especially for anesthesiologists, to increase vigilance against post-anesthesia shivering events to prevent complications after spinal anesthesia